Ardeshir Dadysett Pyaav - Ghosh, Ayan (2023)
Installation of pyaavs to provide drinking water to humans and animals was an act of philanthropy made by prominent members of the various mercantile communities in Mumbai. There are four pyaavs installed inside Jijamata Udyan, which have been restored and are fully functional today, serving drinking water to visitors. Every pyaav, however, has its own indigenous water engineering and water dispensing method.